Metode Mind Mapping untuk Meningkatkan Keterampilan Menulis Surat Pribadi Siswa pada Fase D - Jumadi; Juanda (Universitas Terbuka, 2024)
This writing aims to improve the skills of class VII students at SMP N 3 Karangrayung, in writing personal letters using the mind mapping method. Pre-cycle results show that students' writing motivation is still low, thus affecting learning outcomes. Apart from that, teachers are less innovative in implementing learning methods. This writing is the result of Kurt Lewin's PTK model with a qualitative and quantitative approach. The location of this writing was at SMP N 3 Karangrayung, with the subject being 33 class VII students. Qualitative data collection techniques (observation, interviews, and documentation) and quantitative in the form of formative tests. Data analysis techniques use observation, interviews and documentation techniques, while quantitative through processing formatted test questions with colleagues. Testing the validity of the data includes triangulation tests and using validity and reliability tests. The writing results show that there is an increase in students' personal letter writing skills after implementing the mind mapping model. The stages are carried out in two cycles, namely cycle I and cycle II. The results of the analysis in cycle I showed that 24 students (73%) completed, and in cycle II there was a significant increase, namely 100% completion. So, the mind mapping method is able to improve learning motivation and student learning outcomes in phase D well.